1992
DOI: 10.1073/pnas.89.15.7013
|View full text |Cite
|
Sign up to set email alerts
|

Saccharomyces cerevisiae sec59 cells are deficient in dolichol kinase activity.

Abstract: The temperature-sensitive Saccharomyces cerevisiae mutant sec59 accumulates inactive and incompletely glycosylated protein precursors in its endoplasmic reticulum at the restrictive temperature. O-mannosylation and glycosyl phosphatidylinositol membrane anchoring of protein are also abolished, consistent with a deficiency in dolichyl phosphate mannose. Membranes prepared from sec59 cells that had been shifted to the restrictive temperature, however, made normal amounts of dolichyl phosphate mannose when exogen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
59
1

Year Published

1994
1994
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(63 citation statements)
references
References 43 publications
3
59
1
Order By: Relevance
“…The sec 59-1 strain displays a growth phenotype at non-permissive temperature resulting from a very low pool of DolP (Heller et al,1992). The RER2 gene expressed from the PMA1 promoter Table 4.…”
Section: Mutation Of the Sec59 Protein Affects The Yeast Cell Wallmentioning
confidence: 99%
See 1 more Smart Citation
“…The sec 59-1 strain displays a growth phenotype at non-permissive temperature resulting from a very low pool of DolP (Heller et al,1992). The RER2 gene expressed from the PMA1 promoter Table 4.…”
Section: Mutation Of the Sec59 Protein Affects The Yeast Cell Wallmentioning
confidence: 99%
“…Quantitative measurements showed that the level of dolichyl phosphate in sec 59-1 cells was decreased to 48% of wild-type at the permissive temperature, and to below 10% after the shift of the cells to the restrictive temperature. Analysis of the activity of enzymes from the dolichyl phosphate biosynthetic pathway revealed that the cells are defective in CTP-dependent dolichol kinase activity at both the permissive and the restrictive temperature (Heller et al, 1992). A gene complementing the sec 59 mutation was cloned and sequenced (Bernstein et al, 1989).…”
Section: Introductionmentioning
confidence: 99%
“…Various models have been proposed for these final steps in dolichol biosynthesis (Chojnacki & Dallner, 1988). For example, Heller et al (1992) proposed that once the appropriate isoprenoid chain length has been attained, the a-unsaturated pyrophosphate derivative is dephosphorylated to the monophosphate, followed by a-saturation to yield Dol-P. However, based on [ 3 H]mevalonate labelling studies in membrane fractions, Ekström et al (1987) proposed that terminal isoprene condensation and a-saturation occur cooperatively.…”
Section: Biosynthesis Of the Eukaryotic Dolichyl Lipid Carriersmentioning
confidence: 99%
“…Allen et al (1978Allen et al ( , 1982 first showed CTP-dependent dolichol phosphorylation in mammalian tissues. The CTP-dependent dolichol kinase (DK) in yeast is encoded by sec59 (Heller et al, 1992) which, through complementation studies, led to the cloning of human DK (Fernandez et al, 2002;Shridas & Waechter, 2006). Recently, mutations in DK have been associated with autosomal recessive forms of dilated cardiomyopathy in paediatric patients, extending the genes in dolichol biosynthesis associated with CDGs (Denecke & Kranz, 2009;Kapusta et al, 2013;Kranz et al, 2007;Lefeber et al, 2011).…”
Section: Biosynthesis Of the Eukaryotic Dolichyl Lipid Carriersmentioning
confidence: 99%
“…The a-saturated isoprene is then phosphorylated to form dolichyl phosphate (Dol-P). In yeast, SEC59 encodes the CTP-dependent dolichol kinase and complementation of the yeast sec59-1 conditional mutant with cDNA allowed the identification of the human homolog of SEC59, hDK1 (Heller et al 1992;Fernandez et al 2002).…”
Section: Biosynthesis Of the Lipid-linked Oligosaccharide Dolichol Tmentioning
confidence: 99%